Effects of Ni-loading contents on dehydrogenation kinetics and reversibility of Mg2FeH6. (13th September 2021) - Thiangviriya, Sophida; Plerdsranoy, Praphatsorn; Hagenah, Annbritt; Le, Thi Thu; Kidkhunthod, Pinit; Utke, Oliver; Dornheim, Martin; Klassen, Thomas; Pistidda, Claudio; Utke, Rapee
Abstract: Although Mg2 FeH6 has drawn significant attention for storing hydrogen, its sluggish kinetics during hydrogenation and poor reversibility hinder practical uses. In this work, the replacement of Fe atoms in Mg2 FeH6 with Ni atoms is attempted and the material properties are investigated. A detailed study of the de/rehydrogenation kinetics and reaction mechanisms of the Ni-doped Mg2 FeH6 is carried out. The effects of Ni-loading contents on kinetic properties and behaviors as well as reversibility and reaction pathways are characterized. In addition, the crystal structure of a new Ni-substituted Mg2 FeH6 phase is confirmed. Highlights: Experimental confirmation for the first time of Ni substitution for Fe in Mg2 FeH6 . Studying the effects of Ni-loading contents on desorption kinetics and reversibility. Alteration of de/rehydrogenation pathways with different Ni-loading contents. Enhancement of Mg2 FeH6 reversibility via the formation of Mg2 Fe0.75 Ni0.25 H6 .